Risk factors associated with methicillin-resistant staphylococcus aureus skin and soft tissue infections in hospitalized patients in Colombia (2019)
Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) skin and soft tissue infections (SSTIs) represent a major clinical problem in Colombia. The aim of this study was to evaluate the risk factors associated with MRSA SSTI in Colombia. Methods: A multicenter cohort study with nested case–control design was performed. Patients with an SSTI with at least 48 h of inpatient care were included. Patients with an MRSA SSTI were considered the case group and patients with either a non-MRSA SSTI or with an Methicillin-susceptible S. aureus (MSSA) SSTI were the control groups. A multivariate logistic regression approach was used to evaluate risk factors associated with MRSA SSTI with two different statistical models. Results: A total 1134 patients were included. Cultures were positive for 498 patients, of which 52% (n = 259) were Staphylococcus aureus. MRSA was confirmed in 68.3% of the S. aureus cultures. In the first model, independent risk factors for MRSA SSTI were identified as the presence of abscess (P<0.0001), cellulitis (P = 0.0007), age 18–44 years (P = 0.001), and previous outpatient treatment in the previous index visit (P = 0.003); surgical site infection was a protective factor (P = 0.008). In the second model, the main risk factor found was previous outpatient treatment in the previous index visit (P = 0.013). Conclusions: Community-acquired SSTIs in Colombia are commonly caused by MRSA. Therefore, clinicians should consider MRSA when designing the initial empirical treatment for purulent SSTI in Colombia, although there seems to be low awareness of this fact